2013
DOI: 10.1139/tcsme-2013-0098
|View full text |Cite
|
Sign up to set email alerts
|

Transient Thermo-Stress Field of Brake Shoe During Mine Hoist Emergency Braking

Abstract: In this paper, the finite element (FE) model of the three-dimensional (3-D) transient thermo-stress field of a brake shoe was established and then the software ANSYS 13.0 was used to get the numerical solutions; an experiment was carried out on the X-DM friction tester to verify the FE model. It was found that both the whole temperature and the equivalent stresses of the brake shoe increased and then decreased during mine hoist emergency braking; region of 1 to 3 mm below the friction surface was suffered to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…At 1 mm depth, the temperature value is around 65 C, and at 2 mm, the temperature is lower for almost 20 C than temperature that appeared on the contact surface, what Zhu et al [5] proved in their research. Where this is logical, if the frictional heat generated (heat flux) [27] for the third case is calculated, the following results are obtained: the braking disc heat flux is 91521.41 W/m 2 , and the braking pad heat flux is 11165.71 W/m 2 .…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…At 1 mm depth, the temperature value is around 65 C, and at 2 mm, the temperature is lower for almost 20 C than temperature that appeared on the contact surface, what Zhu et al [5] proved in their research. Where this is logical, if the frictional heat generated (heat flux) [27] for the third case is calculated, the following results are obtained: the braking disc heat flux is 91521.41 W/m 2 , and the braking pad heat flux is 11165.71 W/m 2 .…”
Section: Resultsmentioning
confidence: 69%
“…However, researches that have been studied the transfer of heat through the braking pads indicated that the temperature value decreases with increasing distance from the contact surface with the disc [5].…”
Section: --------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Four sides of brake shoe can be treated as plate. Convection heat transfer coefficient of vertical plate and horizontal plate 16 can be expressed as…”
Section: Random Response Modeling Of the Brake Shoementioning
confidence: 99%
“…Kumar et al 7 investigated the effects of various metallic fillers in friction materials on hot-spot appearance during braking. Zhu et al 8 and Gao and Lin 9 established the three-dimensional transient thermal field model of the brake under constant brake torque during emergency braking. Zhu et al 10 explored frictional catastrophe mechanisms of brake shoe during repetitious emergency braking.…”
Section: Introductionmentioning
confidence: 99%